Thermochemical pre- and biological co-treatments to improve hydrolysis and methane production from poultry wastes - Costa, J. C. (2011)
Poultry industry wastes, namely feathers and poultry litter, are an interesting source of substrate for biogas production. The aim of this work was to assess the biomethane potential of raw poultry wastes, as well as the possibility of enhancing this potential by favouring the hydrolysis of cellulolytic and proteinaceous material in the wastes by using bioaugmentation and thermochemical pre-treatments. Biomethane production from poultry litter and chicken feathers was assessed in batch assays. Pre-treatment with lime and sodium hydroxide was performed at different temperatures and pressures. Clostridium cellulolyticum, C. saccharolyticum and C. thermocellum were used as bioaugmentation strains in the anaerobic digestion of poultry litter. Fervidobacterium pennivorans was used to aid the hydrolysis of poultry feather. Anaerobic digestion of the raw wastes allowed a methanisation percentage (MP) of 17±2 and 33±5%, respectively from poultry litter and chicken feathers, with 2.5% total solids. The major increase in biomethanisation of poultry litter was reached after the thermochemical pre-treatment with Ca(OH)2 (90 °C, 1.27 bar, 120 minutes), with an increase of 15% in the MP comparatively with the raw wastes MP. For the poultry feathers waste, none of the implemented strategies contributed to the optimization of methane production. However, it was observed that all treatments have contributed to a significant increase in the wastes solubilisation. Therefore, the conversion of soluble organic matter to methane was the limiting step of the anaerobic digestion process of poultry wastes.